Stochastic analysis of dynamics the strategic compliance of company Aeroflot - P. A. Mikhnenko (Управленческие науки, 2022)
The use of traditional SWOT-analysis in a dynamic and uncertain external environment does not allow to reasonably form the company’s strategy based on assessments of the state of strengths, weaknesses, opportunities and threats. The reason is that the static assessments of the current state of internal and external factors, obtained from experts, are used to develop a long-term strategy, the implementation of which requires the implementation of organizational changes. The article proposes a new approach to strategic analysis, which consists in evaluating the dynamics of the strategic compliance of factors, taking into account the dispersion of expert opinions (SSMD-analysis). The basis of the algorithm for calculating the final evaluations is the method for determining the optimal intensity of strategic changes. Using the SSMD-analysis methodology based on public data for 2015–2020, an examination of the strategic compliance of factors of the external and internal environment of Aeroflot as of 2020 was conducted. It is concluded that the most relevant direction of the company’s development in 2020 was the accelerated replacement of leased aircraft with its own aircraft. The proposed method makes it possible to assess the dynamic portrait of the company’s interaction with its external environment in conditions of information uncertainty.